Case Report: Malnutrition in an Adult Patient with Chronic Obstructive Pulmonary Disease - Agatha Nadya Lianto; Imelda Wiradarma (Journal La Medihealtico, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic respiratory disorder characterized by persistent airflow obstruction and is frequently accompanied by multiple comorbidities. One of the most common complications among patients with COPD is malnutrition, with approximately 20% of patients experiencing weight loss that contributes to reductions in skeletal muscle mass, respiratory function, and overall quality of life. Case Presentation: A 49-year-old male presented with complaints of dyspnea, cough, epigastric pain, fever, and decreased appetite. The patient had a medical history of COPD and pulmonary tuberculosis, for which treatment had been successfully completed in September 2024. Nutritional screening revealed that the patient appeared markedly underweight, with a body weight of 42 kg, a height of 185 cm, a body mass index (BMI) of 12.27 kg/m², and a mid-upper arm circumference (MUAC) of 18 cm, indicating severe malnutrition. Nutritional intervention was subsequently initiated, consisting of an energy intake of 1,500 kcal/day (38 kcal/kg body weight/day), protein intake of 70 g/day (1.7 g/kg body weight/day), a soft rice-based diet with finely minced high-carbohydrate, high-protein (TKTP) side dishes, supplementation with three eggs daily, and zinc tablets administered at a dosage of one tablet twice daily. Discussion: The provision of high-energy and high-protein nutritional therapy was intended to meet the patient's nutritional requirements, improve nutritional status, and facilitate the restoration of lost muscle mass. The use of a soft diet was expected to reduce postprandial dyspnea, prevent early satiety, and enhance dietary adherence. This case highlights that early nutritional screening and timely nutritional intervention constitute essential components of the comprehensive management of patients with COPD complicated by malnutrition. Long-term monitoring of body weight, nutritional status, and dietary tolerance is necessary to support successful patient rehabilitation and improve clinical outcomes.